Art as horizon. On the link between art and religion in contemporary western culture - Grisales Vargas, Adolfo León (Estudios de Filosofía, 1998)
It is aimed at showing here that art and religion keep a fasten link, no matter the awakening it experiences at particular epochs. In arder to see such link it is completelly necessary not to consider these concepts as disjunctive. In a methodological approach this view implies that it is impossible to the link jiguring each concept separatedly instead of considering the relationship itself as the core. Thematically, on the other hand, it demands to point an artificial the boundaries are in which Western culture is entangled.